Microstructure, hardness and interfacial energy in Co-9Al-10W-xNi (x=15, 25, 35 at. %) alloys during aging - Che C.; Yang S.; Wei M.; Zhang L.; Li Q.; Gao J.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present paper, three Co-Al-W-Ni alloys (i.e., Co-9Al-10W-xNi with x=15, 25, 35 at. %) and their heat treatment mechanisms were carefully designed on the basis of the available phase equilibrium information. The temporal evolution of the microstructure and hardness in the Co-9Al-10W-xNi (x=15, 25, 35) alloys during aging process was measured, from which the effect of additional Ni contents, aging temperature and time on microstructure and hardness in the three Co-Al- W-Ni alloys was analyzed. Considering that the alloy compositions and heat treatment are not directly related with the hardness, the relationship between hardness and microstructure was then linked. It was found that the hardness of Co-based superalloys increases as the volume fraction of γ' precipitates increases, while decreases with the increase of the radius and interval of γ' precipitates. Moreover, the interfacial energy of γ/γ' interface was also evaluated on the basis of the coarsening kinetics of γ' precipitates and the Philippe-Voorhees model in combination with the thermodynamic and atomic mobility databases. The results indicate that the interfacial energies of γ/γ' interface reduce as the increase of additional Ni content and aging temperature.